Rare Germline ATM Variants Influence the Development of Chronic Lymphocytic Leukemia - Lampson, Benjamin L; Gupta, Aditi; Tyekucheva, Svitlana; Mashima, Kiyomi; Petráčková, Anna; Wang, Zixu; Wojciechowska, Natalia; Shaughnessy, Conner J; Baker, Peter O; Fernandes, Stacey M; Shupe, Samantha; Machado, John-Hanson; et al. (Journal of clinical oncology, 2023)
PURPOSE: Germline missense variants of unknown significance in cancer-related genes are increasingly being identified with the expanding use of next-generation sequencing. The ataxia telangiectasia-mutated (ATM) gene on chromosome 11 has more than 1,000 germline missense variants of unknown significance and is a tumor suppressor. We aimed to determine if rare germline ATM variants are more frequent in chronic lymphocytic leukemia (CLL) compared with other hematologic malignancies and if they influence the clinical characteristics of CLL. METHODS: We identified 3,128 patients (including 825 patients with CLL) in our hematologic malignancy clinic who had received clinical-grade sequencing of the entire coding region of ATM. We ascertained the comparative frequencies of germline ATM variants in categories of hematologic neoplasms, and, in patients with CLL, we determined whether these variants affected CLL-associated characteristics such as somatic 11q deletion. RESULTS: Rare germline ATM variants are present in 24% of patients with CLL, significantly greater than that in patients with other lymphoid malignancies (16% prevalence), myeloid disease (15%), or no hematologic neoplasm (14%). Patients with CLL with germline ATM variants are younger at diagnosis and twice as likely to have 11q deletion. The ATM variant p.L2307F is present in 3% of patients with CLL, is associated with a three-fold increase in rates of somatic 11q deletion, and is a hypomorph in cell-based assays. CONCLUSION: Germline ATM variants cluster within CLL and affect the phenotype of CLL that develops, implying that some of these variants (such as ATM p.L2307F) have functional significance and should not be ignored. Further studies are needed to determine whether these variants affect the response to therapy or account for some of the inherited risk of CLL.
Keywords: proteiny buněčného cyklu; Protein Serine-Threonine Kinases; lidé; teleangiektatická ataxie; chronická lymfatická leukemie; Ataxia Telangiectasia Mutated Proteins; ATM protein; mutace; Humans; Ataxia Telangiectasia; Cell Cycle Proteins; Mutation; Tumor Suppressor Proteins; protein-serin-threoninkinasy; nádorové supresorové proteiny; Leukemia, Lymphocytic, Chronic, B-Cell